Makna Simbolik Motif Khas Sarung Ende Lio - Josephina Nirma Rupa; Maria Polencis Pere Ri’a (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to find and describe the symbolic meaning of the typical Ende Lio sarong motif in Nggela Village, Wolojita District, Ende Regency. The method used in this research is descriptive qualitative. The results showed that the symbolic meaning of the typical motif of the Ende Lio sarong in Nggela Village has 5 (five) forms of sarong, each of which has the following form and meaning; (1) the limara sarong contains the meaning of life, love, affection given by the Most Merciful and Merciful God, besides that it also contains the meaning of fertility and beauty; (2) the sarong contains the meaning of sincerity, purity of heart and sincerity of love; (3) the jara elo contains the meaning of a true love struggle; (4) the redu elbow mbira sarong contains the meaning of the twists and turns of human life and the struggle to find true love; (5) the scar cover contains the meaning of the struggle of human life to get love, In conclusion, the five types of typical Ende Lio sarongs each have different motifs and meanings, but still have an element of beauty. Keywords: Ende Lio, Meaning, Motif, Sarong, Symbol